2016
DOI: 10.1002/art.39494
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence and Risk Factors for Psoriatic Arthritis in Patients With Psoriasis: A Prospective Cohort Study

Abstract: Objective. To estimate the incidence of psoriatic arthritis (PsA) in patients with psoriasis, and to identify risk factors for its development.Methods. The study was designed as a prospective cohort study involving psoriasis patients who did not have a diagnosis of arthritis at the time of study enrollment. Information was collected about lifestyle habits, comorbidities, psoriasis activity, and medications. Patients who developed inflammatory arthritis or spondylitis were classified as having PsA if they fulfi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
176
3
22

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 231 publications
(212 citation statements)
references
References 31 publications
(44 reference statements)
9
176
3
22
Order By: Relevance
“…Hence, more than half of the patients with concomitant presence of arthralgia as well as positive MRI changes, but only 15% of patients without such changes developed PsA. Transition of psoriasis into PsA was rather high in our study as compared with other studies,27 which may be based on accumulation of more severe cases including those with beginning joint involvement in the highly specialised care setting of an University Clinic. Nonetheless, these findings indicate the possibility to define patients with psoriasis, in which preventive treatment for the development of PsA may be feasible 28.…”
Section: Discussioncontrasting
confidence: 52%
“…Hence, more than half of the patients with concomitant presence of arthralgia as well as positive MRI changes, but only 15% of patients without such changes developed PsA. Transition of psoriasis into PsA was rather high in our study as compared with other studies,27 which may be based on accumulation of more severe cases including those with beginning joint involvement in the highly specialised care setting of an University Clinic. Nonetheless, these findings indicate the possibility to define patients with psoriasis, in which preventive treatment for the development of PsA may be feasible 28.…”
Section: Discussioncontrasting
confidence: 52%
“…Until now, only one prospective study has been published of patients with psoriasis developing PsA. The study reported a constant risk in these patients 11. Indeed, this finding was corroborated by a cross-sectional observational study of 1560 patients with psoriasis, of which 126 had PsA 19…”
Section: Discussionmentioning
confidence: 91%
“…While recent data suggest an incidence rate ranging from 3.6 to 7.2 per 100 000 person-years, older studies have reported a much wider incidence range (ie, from 0.1 to 23.1 per 100 000 person-years) 6–10. The most recent study and the only prospective study of PsA in patients with psoriasis demonstrated an annual incidence of 2.8% 11. Consequently, the incidence and temporal trends of PsA in the general population remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…A recent prospective cohort study by Eder et al 28 confirmed psoriatic nail lesions and psoriasis severity as risk markers of PsA, while identifying uveitis and low level of education as novel predictors. As more risk factors become elucidated, a risk profile for PsA would enable clinicians to diagnose and provide treatment earlier.…”
Section: Discussionmentioning
confidence: 95%